Features of Chinese realities, linguistic clichés, phraseological units and proper names in fiction translations - Iliychuk, Iryna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
The translation of Chinese phraseological units, proper names, realities and linguistic clichés have always been the focus of attention of Sinologists, teachers, lecturers and translators of the Chinese language. The main task of this study is to determine, highlight and characterize the peculiarities of translation transformations of phraseological units, proper names, realities and linguistic clichés from Chinese to Ukrainian in literary texts. The combination of translation and didactic directions, aimed at in-depth study and substantive application of translated materials in teaching and further scientific activities, will make it possible to bring innovation to the methodology of teaching Chinese in Ukrainian schools and universities and will form a solid foundation for the further development of Ukrainian-Chinese cooperation in humanitarian and cultural spheres.